Explorative healthy aging approaches fostering social innovation: thematizing life course narratives of older women participating in a documentary film - Susie Riva-Mossman; Henk Verloo (Qualitative Research in Medicine & Healthcare, 2017)
The transformative process of investigating life stories and their impact on healthy aging has only recently been explored. The relationship between hope and individual healthy aging strategies is still an under-researched area. This study contributes to filling the knowledgeability gap. The authors examine senior stories of hope and the experience of self-determination and well-being. The study documents the social learning processes of older people as they narratively search for solutions and imagine a hopeful future of healthy aging. A group of four older women participated in a semi-structured filmed interview, questioned by an academic expert. Healthy aging emerged as an important concern among all participants, confirming the need to actively learn how to age well. This exploratory research brought forth thematic clusters, orienting shared value solutions to demographic change. Qualitative research methods reinforce lifelong, collaborative learning processes that not only produce scientific literature, but also put in place relational networks that can grow and endure over time, generating social innovation. The film documented the role of hope and resilience in healthy aging.